Absence of any male-specific antigen recognized by T lymphocytes in X/XSxr' male mice. - McLaren, A (1988)
Previous work has established that whereas X/X mice carrying the sex-reversing chromosomal fragment Sxr are positive for the male-specific transplantation antigen, H-Y, X/X mice carrying the variant Sxr', although they too develop as phenotypic males, are H-Y negative. In this paper we show that X/XSxr' male mice do not express any male-specific antigen that can induce skin-graft rejection.